A potential Cu/V‐organophosphonate platform for tailored void spaces via terpyridine mold casting. Issue 2 (1st April 2017) - Bulut, Aysun; Wörle, Michael; Zorlu, Yunus; Kirpi, Erdogan; Kurt, Huseyin; Zubieta, Jon; Grabowsky, Simon; Beckmann, Jens; Yücesan, Gündoğ
Abstract : A potential Cu/V‐organophosphonate platform for tailored void spaces via terpyridine mold casting is reported. Abstract : The reaction of appropriate copper and vanadium salts with tetratopic methane tetra‐ p ‐phenylphosphonic acid (MTPPA) in the presence of 2, 2′:6′:2′′‐terpyridine (terpy) yielded the three‐dimensional bimetallic copper vanadium phosphonate framework [{Cu(terpy)}4 Cu(VO2 )4 (MTPPA‐H)2 ]·4H2 O (1). Terpy has no net contribution to the three‐dimensional structure providing a potential platform for void space formation via mold‐casting. The structure was characterized by single‐crystal X‐ray diffraction and thermogravimetric analysis (TGA). Magnetic measurements were performed using a SQUID magnetometer. The crystal structure of the methanol solvate of the free ligand, MTPPA·MeOH, was analysed using Hirshfeld surfaces and fingerprint plots.